Inside Cover: (Aza)Pentacenes Clipped into a Ring: Stabilization of Large (Aza)Acenes (Angew. Chem. Int. Ed. 17/2021). Issue 17 (8th March 2021) - Ahrens, Lukas; Tverskoy, Olena; Weigold, Svenja; Ganschow, Michael; Rominger, Frank; Freudenberg, Jan; Bunz, Uwe H. F.
Abstract : Stabilization of large (aza)acenes is a necessary challenge to unlock their full potential. "Clipping" an azaacene into a large ring complements stabilization by trialkylsilylalkynylation as demonstrated by Jan Freudenberg, Uwe H. F. Bunz and co‐workers in their Communication on page 9270 . "Jacketed" azapentacenes display superior photochemical and oxidative stability compared to their bis(TIPS‐ethynyl)‐substituted congeners.